Plant-bacterium interactions analyzed by proteomics - Afroz, Amber; Zahur, Muzna; Zeeshan, Nadia; Komatsu, Setsuko (Frontiers in Plant Science, 2013)
The evolution of the plant immune response has resulted in a highly effective defense system that is able to resist potential attack by microbial pathogens. The primary immune response is referred to as pathogen associated molecular pattern triggered immunity and has evolved to recognize common features of microbial pathogens. In response to the delivery of pathogen effector proteins, plants acquired R proteins to fight against pathogen attack. R-dependent defense response is important in understanding the biochemical and cellular mechanisms and underlying these interactions will enable molecular and transgenic approaches for crops with increased biotic resistance. Proteomic analyses are particularly useful for understanding the mechanisms of host plant against the pathogen attack. Recent advances in the field of proteome analyses have initiated a new research area, i.e the analysis of more complex microbial communities and their interaction with plant. Such areas hold great potential to elucidate, not only the interactions between bacteria and their host plants, but also of bacteria-bacteria interactions between different bacterial taxa, symbiotic, pathogenic bacteria and commensal bacteria. During biotic stress, plant hormonal signaling pathways prioritizes defense over other cellular functions. Some plant pathogens take advantage of hormone dependent regulatory system by mimicking hormones that interfere with host immune responses to promote virulence. In this review, it is discussed the cross talk that plays important role in response to pathogens attack with different infection strategies using proteomic approaches.